Investigation of duty cycle controlled inductive wireless power transfer converter using series-series compensation for electric vehicle application - Bhukya, Bhavsingh; Gotluru, Suresh Babu; Bhukya, Mangu; Bhukya, Ravi Kumar; Dongari, Vaani (Institute of Advanced Engineering and Science, 2024)
This paper presents series-series (SS) compensation topologies that include both primary side duty cycle control (PSDCC) and secondary side duty cycle control (SSDCC) methods. The main challenge for noncontact charging (NCC) for electric vehicles (EVs) batteries, the power transfer capability and efficiency in primary side proved to be unproductive. The investigation considers the primary side control duty cycle control (transmitter and receiver) and the secondary side duty cycle control (transmitter and receiver) in terms of compensation capacitor voltage, coil voltage, load side voltage, current, and power. By adjusting the duty cycle within the range of 0.1 to 0.5, it is possible to control power without significantly decreasing the system's efficiency, by using the SSDCC method. The evaluated parameters, including 1.5 kW output power, 85 kHz resonance frequency, and 120 mm ground clearance, are suitable for three-wheeler auto rickshaws. These findings are verified through MATLAB/Simulink software and compared with experimental results.